Прогнозування споживання електроенергії за допомогою ансамблю моделей машинного навчання - Вишневський, О. К.; Журавчак, Л. М.; Vyshnevskyy, O. K.; Zhuravchak, L. M. (Видавництво Львівської політехніки, 2024)
Досліджено використання моделей машинного навчання для прогнозування електроспоживання інтелектуальної мережі. З’ясовано, що попереднє оброблення даних збільшує продуктивність моделі прогнозування споживання енергії, а методи машинного навчання підвищують її точність завдяки інтеграції кількох алгоритмів та оптимізації гіперпараметрів. Виявлено, що ансамблева модель, яка поєднує низку моделей із різними структурними характеристиками, забезпечує вищу точність прогнозування, ніж кожна модель зокрема. Запропоновано вибір базових моделей із різною будовою: лінійні, рекурсивні, деревоподібні. Вибрано набір даних із часовими рядами кліматичних показників, а також попитом на електроспоживання, досліджено вплив кліматичних характеристик на прогнозовану величину електроспоживання, виконано кореляційний і автокореляційний аналіз. Побудовано базові моделі (авторегресії, регресії опорних векторів, випадкового лісу, довгої короткочасної пам’яті та екстремального посилення градієнта), здійснено їх навчання як слабких учнів та обчислено їхні похибки (середню квадратичну, абсолютну і відносну) між фактичними і прогнозованими значеннями електроспоживання. Здійснено оптимізацію гіперпараметрів базових моделей методом табличного пошуку. Побудовано ансамблеву модель прогнозування (сильного учня) як лінійну комбінацію прогнозів слабких учнів зі зваженими коефіцієнтами. Вагові коефіцієнти для кожного алгоритму оптимізовано за допомогою функції втрат середньоквадратичної похибки за методом найменших квадратів для послідовностей. Встановлено, що запропонована ансамблева модель показала менші значення похибки порівняно із окремими базовими моделями. Тому її використання для прогнозування споживання електроенергії забезпечить вищу точність, ніж кожна окрема базова модель.

The use of machine learning models for electricity consumption prediction for smart grid has been investigated. It was found that data pre-processing can improve the performance of the energy consumption prediction model, while machine learning algorithms can improve model prediction accuracy through the integration of multiple algorithms and hyperparameter optimization. It was found that the ensemble learning method can provide better prediction accuracy than each individual method by combining the strong features of different methods that have different structural characteristics. Based on this idea, a choice of basic models with different structures was offered – linear, recursive, tree-like. We have used for research publicly available dataset containing time series of electric power demand and weather data. The influence of climatic characteristics on the predicted value (electric power demand) was studied, correlation and autocorrelation analysis were carried out. Individual basic models for electric power demand prediction were built and trained using Autoregression, Support Vector Regression, Random Forest, Long Short-Term Memory and Extreme Gradient Boosting. Thentesting of forecasting errors (Root Mean Squared Error, Mean Absolute Error, Mean Absolute Percentage Error) between actual power consumption and predicted values was carried out. Optimization of the hyperparameters of each weak learner of the integrated model was carried out using the grid search method. An ensemble model (strong learner) for forecasting electricity consumption based linear combination of several basic models' forecasts (weak learners) with weighting coefficients was presented. The weighting coefficients of individual models' forecasts have been established and then optimized using the root-mean-square error loss function with the sequential least-squares optimization algorithm. It was established that the proposed ensemble model for forecasting electricity consumption showed smaller error metrics compared to individual basic models. Therefore, the results demonstrated the effectiveness of our proposed ensemble model, it can be used to predict electricity consumption with greater accuracy and outperform the individual models with different structure, considering each base models' advantages.
Forecasting the electricity consumption using an ensemble of machine learning models
Keywords: часові ряди; регресія; енергія; потужність; нейронні мережі; time series; regression; energy; power; neural networks